Europa: um projecto em construção Homenagem a David Sassoli - Graziani, Michela; Rita, Annabela (Libere carte, 2023)
The volume, created by the collaboration between the University of Florence and the University of Lisbon, aims to celebrate the President of the European Parliament, David Sassoli, a year after his death in january 2022. The miscellaneous volume, entirely written in Portuguese language, includes 36 works among essays, poems, novels, drawings, paintings starting with the figure and the European values that have so strongly been defended by David Sassoli, to reflect on the future of Europe and new geopolitical scenarios that Europe is going through, after the death of the President of the European Parliament.